Preparation method of composite calcium phosphate bone cement

By mineralizing the additive phase in a calcium-phosphate solution and mixing it with calcium-phosphate bone cement to form composite calcium-phosphate bone cement, the problem of doping materials affecting the curing rate is solved, and the high compressive strength and biological activity of the material are achieved. Ensures stability and biocompatibility of curing time.

CN119318732APending Publication Date: 2025-01-17ZHUHAI NAJIN HEALTH TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411440521.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

After adding doped materials, the curing rate changes in existing calcium phosphate bone cements affect their use effect, and it is difficult to simultaneously improve compressive strength and biological activity without affecting the curing rate.

Method used

By soaking the additive phase in a solution containing calcium and phosphorus for mineralization, a modified additive phase is formed, and mixed with the calcium phosphate bone cement powder and then mixed with the aqueous phase to cure it to form composite calcium phosphate bone cement, avoiding relative addition curing The influence of time also improves the stability and biological activity of the material.

Benefits of technology

The good compressive strength and biological activity of composite calcium phosphate bone cement is achieved, the stability of curing time is ensured, the significant impact of doped materials on the curing rate is avoided, and the biocompatibility and use effect of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318732A_ABST
    Figure CN119318732A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological material preparation, in particular to a preparation method of composite calcium phosphate bone cement. The preparation method provided by the invention comprises the following steps: soaking an adding phase into a solution containing calcium and phosphorus, and mineralizing to obtain a modified adding phase; mixing the modified additive phase with calcium phosphate bone cement powder to obtain mixed powder; and mixing the mixed powder and a water phase into paste, and curing to obtain the composite calcium phosphate bone cement. The method is simple in preparation process, and the additive phase can be used only by soaking the additive phase in a calcium-phosphorus solution and then centrifugally drying; the formation of the calcium phosphate coating does not influence the chemical composition of the additive phase, but the influence of the additive phase on the curing time of the calcium phosphate bone cement can be remarkably avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomaterials, and in particular to a method for preparing composite calcium phosphate bone cement. Background Art

[0002] With the aging of the population and the frequent occurrence of sports injuries, the demand for the treatment of fractures and bone defects is increasing, and the demand for bone repair materials is also growing. Among the many bone repair materials, calcium phosphate cement (CPC) has extensive value in the field of bone repair due to its excellent biocompatibility, good osteoinductivity and easy shaping.

[0003] The curing time of calcium phosphate bone cement is a key factor in its clinical application effect, which directly affects the operability of the operation, the speed of bone integration of the material and the final treatment effect. The appropriate curing time not only ensures that the doctor has enough time to accurately operate and shape the material, but also helps to speed up the patient's recovery process and reduce postoperative complications.

[0004] Although the addition of additives can improve the compressive strength, bioactivity and injectability of calcium phosphate cement, it will also affect the curing rate of calcium phosphate cement. For example, the addition of citrate can affect the curing process of calcium phosphate cement, thereby prolonging its plasticity time. The addition of boric acid and borates has also been shown to effectively interfere with the original curing reaction and prolong the initial setting time of the material. The addition of bioactive glass, polylactic acid, gelatin, chitosan, etc. will also affect the curing process of calcium phosphate cement, resulting in changes in the curing time.

[0005] Therefore, the influence of doping material (addition phase) on the setting rate of calcium phosphate bone cement can hinder its use to calcium phosphate bone cement, and for this reason, it is necessary to propose a solution, which can improve the properties such as the compressive strength, biological activity of calcium phosphate bone cement itself by doping material, while not significantly affecting the setting rate of calcium phosphate bone cement itself. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a preparation method of a composite calcium phosphate bone cement. The preparation method provided by the present invention does not affect the curing rate of the calcium phosphate bone cement itself, and the prepared composite calcium phosphate bone cement has good compressive strength and biological activity.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a composite calcium phosphate bone cement, comprising the following steps:

[0009] soaking the added phase in a solution containing calcium and phosphorus to carry out mineralization, thereby obtaining a modified added phase;

[0010] Mixing the modified additive phase and calcium phosphate bone cement powder to obtain a mixed powder;

[0011] The mixed powder and water are mixed into a paste and then solidified to obtain composite calcium phosphate bone cement.

[0012] Preferably, the soaking time is 1 to 30 days.

[0013] Preferably, the mass ratio of the added phase to the volume ratio of the calcium-phosphorus-containing solution is 1 g: 100-1000 mL.

[0014] Preferably, the particle size of the added phase is 50 nm to 1000 μm.

[0015] Preferably, the material of the added phase is bioceramics, polymer materials, metals or composite materials;

[0016] The composite material is a composite of at least two of bioceramics, polymer materials and metals.

[0017] Preferably, the polymer material comprises one or more of polylactic acid, polycaprolactone, chitosan, polylactic acid-co-glycolic acid, calcium alginate, collagen, gelatin, hyaluronic acid, polydioxanone, polyhydroxyalkanoate, polytrimethylene carbonate, polyurethane, polyether urethane and polysaccharide;

[0018] The metal includes one or more of titanium, titanium alloy, stainless steel, magnesium, magnesium alloy, zinc, zinc alloy and cobalt-chromium alloy.

[0019] Preferably, the bioceramic comprises one or more of bioactive glass, zirconium oxide, calcium sulfate, calcium phosphate, calcium polyphosphate, magnesium phosphate, calcium silicate, calcium carbonate, magnesium polyphosphate, perovskite and barium titanate.

[0020] Preferably, the mass of the modified additive phase is 0.1 to 60% of the mass of the mixed powder.

[0021] Preferably, the aqueous phase is one or more of pure water, physiological saline, disodium hydrogen phosphate solution, sodium dihydrogen phosphate solution, PBS aqueous solution and SBF biomimetic solution.

[0022] Preferably, the calcium phosphate bone cement powder includes one or more of anhydrous monocalcium phosphate, monocalcium phosphate monohydrate, octacalcium phosphate, tetracalcium phosphate, anhydrous dicalcium phosphate, α-tricalcium phosphate, β-tricalcium phosphate, calcium-deficient hydroxyapatite, dibasic calcium phosphate dihydrate and amorphous calcium phosphate.

[0023] The present invention provides a method for preparing a composite calcium phosphate bone cement, comprising the following steps: immersing an added phase in a solution containing calcium and phosphorus for mineralization to obtain a modified added phase; mixing the modified added phase with a calcium phosphate bone cement powder to obtain a mixed powder; and solidifying the mixed powder and an aqueous phase after mixing them into a paste to obtain a composite calcium phosphate bone cement. The calcium phosphate coating formed in the modified added phase of the present invention does not affect the chemical composition, mechanical properties, degradation properties and biocompatibility of the added phase itself, but can significantly avoid the influence of the added phase on the curing time of the calcium phosphate bone cement. The curing time of the calcium phosphate bone cement does not change by more than 20 minutes due to the addition of the added phase. In addition, the addition of the added phase improves the stability of the calcium phosphate bone cement, providing a strategy for the doping modification of the calcium phosphate bone cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The compressive strength of the modified bioactive glass-doped calcium phosphate bone cement in different proportions in Example 1;

[0025] Figure 2 The CCK-8 results of mouse osteoblasts cultured in the modified bioactive glass-doped calcium phosphate bone cement of the embodiment and the comparative example for 1 day and 3 days. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a composite calcium phosphate bone cement, comprising the following steps:

[0027] soaking the added phase in a solution containing calcium and phosphorus to carry out mineralization, thereby obtaining a modified added phase;

[0028] Mixing the modified additive phase and calcium phosphate bone cement powder to obtain a mixed powder;

[0029] The mixed powder and water are mixed into a paste and then solidified to obtain composite calcium phosphate bone cement.

[0030] The invention soaks the additive phase into a solution containing calcium and phosphorus for mineralization to obtain the modified additive phase.

[0031] In the present invention, before the additional phase is immersed in the calcium-phosphorus-containing solution, it is preferred that the additional phase is subjected to surface modification treatment.

[0032] In the present invention, the surface modification treatment method is preferably plasma treatment, physical adsorption, high-energy radiation, coating, chemical polymerization, biomolecule adsorption or grafting, acid-base treatment, enzyme or protein grafting, heat treatment or nano-modification.

[0033] In the present invention, the material of the added phase is bioceramics, polymer materials, metals or composite materials;

[0034] The composite material is a composite of at least two of bioceramics, polymer materials and metals.

[0035] In the present invention, the calcium-phosphorus-containing solution preferably includes: one or more of SBF simulated body fluid, hydroxyapatite saturated solution, high phosphate mineralization solution, acidic mineralization solution, simulated seawater mineralization solution, cell mineralization solution, calcium-rich mineralization solution, organic solvent-assisted mineralization solution, nanoparticle-assisted mineralization solution, dynamic mineralization solution, temperature gradient mineralization solution and biomolecule-assisted mineralization solution.

[0036] In the present invention, the volume ratio of the mass of the added phase to the calcium-phosphorus-containing solution is preferably 1 g:100-1000 mL, more preferably 1 g:200 mL.

[0037] In the present invention, the modified additive phase is preferably a core-shell structure; the core is preferably an additive phase; and the material of the shell is preferably a coating layer whose main component is calcium phosphate.

[0038] In the present invention, the soaking time is preferably 1 to 30 days.

[0039] After obtaining the modified additive phase, the present invention mixes the modified additive phase with calcium phosphate bone cement powder to obtain a mixed powder.

[0040] In the present invention, the calcium phosphate bone cement powder preferably includes one or more of anhydrous monocalcium phosphate (MCPA), monocalcium phosphate monohydrate (MCPM), octacalcium phosphate (OCP), tetracalcium phosphate (TTCP), anhydrous dicalcium phosphate (DCPA), dibasic calcium phosphate dihydrate (DCPD), α-tricalcium phosphate (α-TCP), β-tricalcium phosphate (β-TCP), calcium-deficient hydroxyapatite (CDHA) and amorphous calcium phosphate (ACP).

[0041] In the present invention, the mass of the modified additive phase is preferably 0.1 to 60% of the mass of the mixed powder, and more preferably 5 to 20%.

[0042] In the present invention, the mass ratio of the modified additive phase to calcium phosphate bone cement is preferably 0.01-20:80-99.99.

[0043] After obtaining the mixed powder, the present invention mixes the mixed powder with water into a paste and then solidifies it to obtain composite calcium phosphate bone cement.

[0044] In the present invention, the aqueous phase is preferably one or more of pure water, physiological saline, disodium hydrogen phosphate solution, sodium dihydrogen phosphate solution, PBS aqueous solution and SBF biomimetic solution.

[0045] In the present invention, when the aqueous phase is a disodium hydrogen phosphate solution, the concentration of the disodium hydrogen phosphate solution is preferably 0.15 to 0.25 mol / L, more preferably 0.2 mol / L.

[0046] In the present invention, the dosage ratio of the mixed powder and the disodium hydrogen phosphate solution is preferably 1 g:0.4 mL.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] (1) 1 g of 45S5 bioactive glass (from Foshan Jinlan Biotechnology Co., Ltd., product batch number T80123B103) was placed in 200 mL of SBF simulated body fluid and allowed to stand for 7 days (the liquid was changed every 3 days). The supernatant was removed by centrifugation, washed 3 times with deionized water, and dried at 50°C for 5 h to obtain SBF-BG powder.

[0050] (2) 0.95 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and α-tricalcium phosphate in a mass ratio of 1:9) and 0.05 g of SBF-BG were placed in a sealed container, and the powder was shaken on an oscillator for 2 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution was added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with bioactive glass (denoted as CPG-5%).

[0051] Example 2

[0052] The only difference from Example 1 is that 0.9 g of calcium phosphate bone cement powder and 0.1 g of SBF-BG (denoted as CPG-10%) are added in step (2).

[0053] Example 3

[0054] The only difference from Example 1 is that 0.8 g of calcium phosphate bone cement powder and 0.2 g of SBF-BG (denoted as CPG-20%) are added in step (2).

[0055] Example 4

[0056] (1) 1 g of 58s bioactive glass (from Kunshan Huaqiao Technology New Materials Co., Ltd., model specification: HQ-BG58s-02) was placed in 200 mL of SBF simulated body fluid and allowed to stand for 7 days (the liquid was changed every 3 days). The supernatant was removed by centrifugation, washed 3 times with deionized water, and dried at 50 °C for 5 h to obtain SBF-58s powder.

[0057] (2) 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of anhydrous dicalcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.1 g of SBF-58s were placed in a sealed container, and the powder was shaken on an oscillator for 3 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution was added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with bioactive glass (58s).

[0058] Example 5

[0059] (1) 1 g of 85s bioactive glass (from Merck KGaA, product number 916072) was placed in 200 mL of SBF simulated body fluid and allowed to stand for 7 days (the solution was changed every 3 days). The supernatant was removed by centrifugation, washed 3 times with deionized water, and dried at 50°C for 5 h to obtain SBF-85s powder.

[0060] (2) 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.1 g of SBF-BG were placed in a sealed container, and the powder was shaken on an oscillator for 3 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution was added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with bioactive glass (85s).

[0061] Example 6

[0062] (1) 1 g of titanium powder was placed in 200 mL of SBF simulated body fluid and allowed to stand for 7 days (the fluid was changed every 3 days). The supernatant was removed by centrifugation, washed 3 times with deionized water, and dried at 50 °C for 6 h to obtain SBF-Ti powder.

[0063] (2) 0.8 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of monocalcium phosphate monohydrate and β-tricalcium phosphate in a mass ratio of 1:4) and 0.2 g of SBF-Ti are placed in a sealed container and shaken for 2 min using an oscillator to fully mix the powder. Then 400 μL of 0.25 mol / L disodium hydrogen phosphate solution is added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified titanium powder.

[0064] Example 7

[0065] (1) 1 g of polylactic acid powder (PLA) was placed in 200 mL of SBF simulated body fluid and allowed to stand for 14 days (the fluid was changed every 3 days). The supernatant was removed by centrifugation, and the mixture was washed 3 times with deionized water and dried at 50°C for 5 h to obtain SBF-PLA powder.

[0066] (2) 0.8 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of calcium-deficient hydroxyapatite and α-tricalcium phosphate in a mass ratio of 1:5) and 0.2 g of SBF-PLA are placed in a sealed container and shaken for 2 minutes using an oscillator to fully mix the powder. Then, 400 μL of 0.15 mol / L disodium hydrogen phosphate solution is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified polylactic acid powder.

[0067] Example 8

[0068] (1) 1 g of magnesium oxide powder was placed in 200 mL of SBF simulated body fluid and allowed to stand for 14 days (the fluid was changed every 3 days). The supernatant was removed by centrifugation, and the mixture was washed 3 times with deionized water and dried at 50°C for 5 h to obtain SBF-MgO powder.

[0069] (2) 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of monocalcium phosphate monohydrate and β-tricalcium phosphate in a mass ratio of 1:4) and 0.1 g of SBF-MgO are placed in a sealed container and shaken for 2 min using an oscillator to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution is added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified magnesium oxide powder.

[0070] Example 9

[0071] (1) 1 g of titanium alloy powder (TC4) was placed in 200 mL of 1.5 times SBF simulated body fluid and allowed to stand for 14 days (the fluid was changed every 3 days). The supernatant was removed by centrifugation, washed 3 times with deionized water, and dried at 50°C for 5 h to obtain SBF-TC4 powder.

[0072] (2) 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:5) and 0.1 g of SBF-TC4 are placed in a sealed container and shaken for 2 min using an oscillator to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution is added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified TC4.

[0073] Example 10

[0074] (1) 1 g of polycaprolactone (PCL) was placed in 200 mL of 1.5 times SBF simulated body fluid and allowed to stand for 14 days (the fluid was changed every 3 days). The supernatant was removed by centrifugation, and the mixture was washed 3 times with deionized water and dried at 50°C for 5 h to obtain SBF-PCL powder.

[0075] (2) 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of β-tricalcium phosphate and α-tricalcium phosphate in a mass ratio of 1:5) and 0.1 g of SBF-PCL are placed in a sealed container and shaken for 2 min using an oscillator to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate solution is added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified PCL.

[0076] Embodiment 11

[0077] (1) Place 1 g of calcium carbonate in 200 mL of saturated hydroxyapatite solution and let it stand for 14 days (change the solution every 3 days). Then remove the supernatant by centrifugation, wash with deionized water 3 times, and dry at 50 °C for 5 h to obtain HA-CaCO3 powder.

[0078] (2) 0.8 g of calcium phosphate bone cement powder (acid calcium bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.2 g of HA-CaCO3 are placed in a sealed container and shaken for 2 min using an oscillator to fully mix the powder. Then 400 μL of 0.25 mol / L disodium hydrogen phosphate solution is added and stirred for 3 min to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with modified CaCO3.

[0079] Comparative Example 1

[0080] 1 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and α-tricalcium phosphate in a mass ratio of 1:9) was added with 400 μL of 0.25 mol / L disodium hydrogen phosphate solution and stirred for 3 min to form a uniform paste material to obtain a composite calcium phosphate bone cement doped with bioactive glass (denoted as CPC).

[0081] Comparative Example 2

[0082] 0.95 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and α-tricalcium phosphate in a mass ratio of 1:9) and 0.05 g of BG were placed in a closed container, and an oscillator was used to oscillate for 2 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate was added and stirred for 3 min to form a uniform paste material to obtain a composite calcium phosphate bone cement doped with bioactive glass (denoted as CPC-BG-5%).

[0083] Comparative Example 3

[0084] The only difference from Comparative Example 2 is that the formula ratio is changed to 0.9g calcium phosphate bone cement powder and 0.1g BG (denoted as CPC-BG-10%).

[0085] Comparative Example 4

[0086] 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of anhydrous dicalcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.1 g of bioactive glass (58s) were placed in a closed container, and the powder was shaken on an oscillator for 3 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate was added and stirred for 3 min to form a uniform paste material to obtain a composite calcium phosphate bone cement doped with bioactive glass (58s).

[0087] Comparative Example 5

[0088] 0.9 g of calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.1 g of bioactive glass (85s) were placed in a closed container, and the powder was shaken on an oscillator for 3 min to fully mix the powder. Then, 400 μL of 0.25 mol / L disodium hydrogen phosphate was added and stirred for 3 min to form a uniform paste material to obtain a composite calcium phosphate bone cement doped with bioactive glass (85s).

[0089] Comparative Example 6

[0090] 0.8g calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of monocalcium phosphate monohydrate and β-tricalcium phosphate in a mass ratio of 1:4) and 0.2g Ti powder are placed in a closed container and shaken with an oscillator for 2 minutes to fully mix the powder. Then 400μL 0.25mol / L disodium hydrogen phosphate is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with titanium powder.

[0091] Comparative Example 7

[0092] 0.8g calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of calcium-deficient hydroxyapatite and α-tricalcium phosphate in a mass ratio of 1:5) and 0.2g PLA powder are placed in a closed container and shaken with an oscillator for 2 minutes to fully mix the powder. Then 400μL 0.15mol / L disodium hydrogen phosphate is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with polylactic acid powder.

[0093] Comparative Example 8

[0094] 0.9g calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of monocalcium phosphate monohydrate and β-tricalcium phosphate in a mass ratio of 1:4) and 0.1g magnesium oxide powder are placed in a closed container and shaken with an oscillator for 2 minutes to fully mix the powder. Then 400μL 0.25mol / L disodium hydrogen phosphate is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with magnesium oxide powder.

[0095] Comparative Example 9

[0096] 0.9g calcium phosphate bone cement powder (calcium phosphate bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:5) and 0.1g TC4 powder are placed in a closed container and shaken for 2 minutes using an oscillator to fully mix the powder. Then 400μL 0.25mol / L disodium hydrogen phosphate is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with TC4 powder.

[0097] Comparative Example 10

[0098] 0.9g calcium phosphate bone cement powder (specifically, calcium phosphate bone cement powder is a mixture of β-tricalcium phosphate and α-tricalcium phosphate in a mass ratio of 1:5) and 0.1g polycaprolactone (PCL) powder were placed in a closed container and vibrated on an oscillator for 2 minutes to fully mix the powder. Then 400μL 0.25mol / L disodium hydrogen phosphate was added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with PCL powder.

[0099] Comparative Example 11

[0100] 0.8g calcium phosphate bone cement powder (acid calcium bone cement powder is a mixture of dihydrate calcium phosphate and tetracalcium phosphate in a mass ratio of 1:4) and 0.2g calcium carbonate (CaCO3) powder are placed in a closed container and shaken with an oscillator for 2 minutes to fully mix the powder. Then 400μL 0.25mol / L disodium hydrogen phosphate is added and stirred for 3 minutes to form a uniform paste material and then solidified to obtain a composite calcium phosphate bone cement doped with CaCO3 powder.

[0101] The paste materials prepared in the comparative example and the example were filled into a circular mold with a diameter of 6 mm and a height of 12 mm, and the curing time was tested using a Vicat apparatus. The results are shown in Table 1.

[0102] Table 1 Curing time of modified bioactive glass-doped calcium phosphate bone cement in Examples and Comparative Examples

[0103]

[0104]

[0105] The compressive strength of the materials prepared in Comparative Example 1 and Examples 1 to 3 was tested using a universal mechanical testing machine (computer-controlled electronic universal material testing machine HY-0580). Before testing the compressive strength, the composite cement was fully cured for 3 days in a constant temperature and humidity environment. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the compressive strengths of pure calcium phosphate cement (CPC), CPG-5% and CPG-10% are similar, all between 25 MPa and 30 MPa, which indicates that the addition of modified BG has no significant effect on the compressive strength of the bone cement system.

[0106] Cell Counting Kit-8 (CCK-8, Beyotime Biotechnology, China) was used to detect the proliferation effects of mouse embryonic osteoblast precursor cells (MC3T3-E1) on different cement extracts. CPC was used as a control, CPG-5%, CPG-10%, and CPG-20% extracts were used as culture media, and standard growth medium was used as a control group for cell culture. The samples to be tested were placed under ultraviolet light overnight, and then the samples were immersed in Minimum Essential Medium (MEM) at a solid-liquid volume ratio of 0.1g / mL at 37°C for 24 hours. The cells were first seeded in a 96-well plate at a density of 5000 cells per well. After culturing for 24 hours at 37°C and 5% humid CO2 atmosphere, 100μL of sample extract was added to the regular culture medium. After 1 and 3 days of cell culture, the culture medium was removed, rinsed twice with phosphate-buffered saline (PBS), and 110μL of CCK-8 dilute solution was added to each well and incubated for 3 hours in the dark. 100 μL of the diluted CCK-8 solution was transferred from each well to a new 96-well plate, and the optical absorbance at a wavelength of 450 nm was measured using a microplate reader (DNM-9602, PERLONG, USA). Figure 2 The CCK-8 results of mouse osteoblasts cultured with CPC-doped bioactive glass after modification in Comparative Example 1 and Examples 1 to 3 for 1 day and 3 days are shown in Table 1. Figure 2 It can be seen that all groups have good biocompatibility, low cytotoxicity and good biosafety performance, that is, surface mineralization treatment will not have a negative impact on the biocompatibility of additives.

[0107] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite calcium phosphate bone cement, characterized in that, The following steps are involved: soaking the added phase in a solution containing calcium and phosphorus to carry out mineralization, thereby obtaining a modified added phase; Mixing the modified additive phase and calcium phosphate bone cement powder to obtain a mixed powder; The mixed powder and water are mixed into a paste and then solidified to obtain composite calcium phosphate bone cement.

2. The preparation method according to claim 1, characterized in that The soaking time is 1 to 30 days.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the added phase to the volume ratio of the calcium-phosphorus-containing solution is 1 g:100-1000 mL.

4. The preparation method according to claim 1, characterized in that: The particle size of the added phase is 50nm-1000μm.

5. The preparation method according to claim 4, characterized in that: The material of the added phase is bioceramics, polymer materials, metals or composite materials; The composite material is a composite of at least two of bioceramics, polymer materials and metals.

6. The preparation method according to claim 5, characterized in that: The polymer material includes one or more of polylactic acid, polycaprolactone, chitosan, polylactic acid-glycolic acid copolymer, calcium alginate, collagen, gelatin, hyaluronic acid, polydioxanone, polyhydroxyalkanoate, polytrimethylene carbonate, polyurethane, polyether urethane and polysaccharide; The metal includes one or more of titanium, titanium alloy, stainless steel, magnesium, magnesium alloy, zinc, zinc alloy and cobalt-chromium alloy.

7. The preparation method according to claim 5, characterized in that: The bioceramic includes one or more of bioactive glass, zirconium oxide, calcium sulfate, calcium phosphate, calcium polyphosphate, magnesium phosphate, calcium silicate, calcium carbonate, magnesium polyphosphate, perovskite and barium titanate.

8. The preparation method according to claim 1, characterized in that: The mass of the modified additive phase is 0.1 to 60% of the mass of the mixed powder.

9. The preparation method according to claim 1, characterized in that: The aqueous phase is one or more of pure water, physiological saline, disodium hydrogen phosphate solution, sodium dihydrogen phosphate solution, PBS aqueous solution and SBF biomimetic solution.

10. The preparation method according to claim 1, characterized in that: The calcium phosphate bone cement powder includes one or more of anhydrous monocalcium phosphate, monocalcium phosphate monohydrate, octacalcium phosphate, tetracalcium phosphate, anhydrous dicalcium phosphate, α-tricalcium phosphate, β-tricalcium phosphate, calcium-deficient hydroxyapatite, dibasic calcium phosphate dihydrate and amorphous calcium phosphate.